Advanced Decision Making - Band John (Financial Times Management, 1999)
Introduction, The Nature of Managerial Decision Making, Models of Decision Making, Using the Rational Model for Systematic Decision Making, Decision-Making Aids, The Psychology of Decision Making, Group Decision Making, Organisational Decision Making, Further Reading and References, References.
Introduction, The Nature of Managerial Decision Making, Models of Decision Making, Using the Rational Model for Systematic Decision Making, Decision-Making Aids, The Psychology of Decision Making, Group Decision Making, Organisational Decision Making, Further Reading and References, References.